2010
DOI: 10.1124/dmd.110.034710
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Based Inactivation of Human CYP2E1 by Diethyldithocarbamate

Abstract: ABSTRACT:Although the ability of disulfiram to inactivate CYP2E1 has been known for more than 20 years, the mechanism has not yet been

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 24 publications
1
17
1
Order By: Relevance
“…A recent study identified diethyldithiocarbamate as the inhibitory metabolite; mass spectrometry indicated formation of a mixed disulfide between this metabolite and the apo-enzyme [54]. However, in this study, enzyme activity could not be restored by reductive cleavage of the disulfide, suggesting that the enzyme had incurred additional changes, for example the binding of another metabolite to its prosthetic heme group.…”
Section: Inhibition Of Cyp2e1contrasting
confidence: 47%
See 1 more Smart Citation
“…A recent study identified diethyldithiocarbamate as the inhibitory metabolite; mass spectrometry indicated formation of a mixed disulfide between this metabolite and the apo-enzyme [54]. However, in this study, enzyme activity could not be restored by reductive cleavage of the disulfide, suggesting that the enzyme had incurred additional changes, for example the binding of another metabolite to its prosthetic heme group.…”
Section: Inhibition Of Cyp2e1contrasting
confidence: 47%
“…The drug disulfiram inhibits both CYP2E1 and aldehyde dehydrogenase. formed by glutathione-dependent reduction and inhibits CYP2E1 [54]. The second metabolite, S-ethyl-N,N-diethylthiolcarbamate sulfoxide (DETC-MeSO), inhibits aldehyde dehydrogenase; several cytochrome P450 enzymes participate in its formation from DDTC [50].…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…The mechanism by which alkyl xanthates inactivate CYP2B1 was investigated by examining the effects of C8 on the individual steps of the CYP2B1 catalytic cycle [372] Dramatic losses in the 7-EFC activity of CYP2B1 were observed when it was incubated with five different xanthates in the presence of NADPH With the exception of the C14 xanthate, there was virtually no loss in the heme absorbance at 418 nm or in the absorbance of the reduced-CO complex at 450 nm The long-chain xanthates reduced the rate of the transfer of the first electron in the P450 catalytic cycle by stabilizing the heme in its low spin state C8 led to very little formation of the oxy-ferryl intermediate complex The rates of reduction of the native, C8-exposed, and C8-inactivated CYP2B1 by CPR were measured [372] The rate of reduction of the C8-inactivated P450 was approximately 62 % slower when compared to that of the native enzyme either in the absence or presence of benzphetamine The formation of products from benzphetamine by the three enzyme preparations was determined [372] The C8-inactivated CYP2B1 exhibited a much lower rate of NADPH consumption and formation of the formaldehyde product In addition, the ratio of H 2 O 2 to formaldehyde increased from 1:1 for the unmodified enzyme to 28:1 for the inactivated CYP2B1 [372] Thus, these observations suggest that the reactive intermediate formed from the C8-xanthate causes covalent modification of the CYP2B1 apoprotein, which reduces the rate of the first electron transfer by CPR and also leads to the uncoupling of product formation from electron transfer by diverting a greater proportion of the electrons to the formation of H 2 O 2 rather than product formation [372] Disulfiram (Antabuse) has been used therapeutically for the treatment of alcoholism for more than 60 years because of its ability to inhibit aldehyde dehydrogenase Another enzyme that is inhibited by disulfiram is human CYP2E1 [373] [373] LC-MS of the inactivated CYP2E1 demonstrates that the inactivation results from the formation of an adduct of the reactive metabolite of DDC with the apoprotein MS studies of the GSH-adduct formed by the reactive intermediate indicate that the reactive intermediate has a mass of 116 Da HPLC analysis of the inactivated protein mixture showed no change in the amount of unmodified heme or the presence of any modified heme [373] These results suggest that binding of the reactive intermediate to the apoprotein involves formation of a disulfide bond with one of the eight cysteines in CYP2E1 Incubation of the modified protein in the presence of DTT resulted in the loss of the DDC adduct and reversal of the mass of the CYP2E1 to that of the unmodified protein However, no regain of activity following loss of the DDC adduct could be observed These results support the hypothesis that adduct formation leads to a disulfide bond In addition to investigating the inactivation of wild-type CYP2E1, the inactivation of two of its polymorphic mutants, CYP2E12 and CYP2E14 was also investigated For the wild-type enzyme, the K I was 122 µM and the k inact was 002 min − 1 The K I values for the two polymorphic mutants were 2276 and 124 µM for CYP2E12 and CYP2E14 and the k inact values were 00061 and 00187 min − 1 , respectively These results demonstrate that DDC is much less efficient as an inactivator of CYP2E12 than it is of either the wild-type or the CYP2E14 variant …”
Section: Organosulfur and Halogenated Compoundsmentioning
confidence: 99%
“…The plasmids for the Nterminal truncated and C-terminal His-tagged CYP2B4dH (hereon referred to as CYP2B4) and human CYP2E1 were a generous gift from Dr. James Halpert. These two P450s and the CYP2E1 Y422D variant were overexpressed in E. coli C41 (DE3) cells separately and purified using a Ni-NTA affinity column as described previously (Scott et al, 2003;Pratt-Hyatt et al, 2010). The concentrations of CYP2B4 and CYP2E1 were determined using an extinction coefficient of Δ« 450-490 nm of 91 mM 21 cm 21 as described by Omura and Sato, 1964.…”
Section: Methodsmentioning
confidence: 99%